2007
DOI: 10.1007/s12034-007-0052-3
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of CeO2 thin films

Abstract: Cerium oxide (CeO 2 ) thin films have been prepared by electron beam evaporation technique onto glass substrate at a pressure of about 6 × 10 -6 Torr. The thickness of CeO 2 films ranges from 140-180 nm. The optical properties of cerium oxide films are studied in the wavelength range of 200-850 nm. The film is highly transparent in the visible region. It is also observed that the film has low reflectance in the ultra-violet region. The optical band gap of the film is determined and is found to decrease with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 15 publications
5
31
1
Order By: Relevance
“…In this study, despite the decreased degree of conversion observed by increasing CeO2 addition, all groups showed values around 50%, which is in accordance with commercial dental adhesives [38]. Therefore, CeO2 = 2.2 to 2.8) [30], which may have decreased the accessibility of light energy inside the polymer. The limited mobility of monomer chains by the incorporation of the opaque fillers has also been considered as a contributing factor for the decrease in the monomer's conversion [31].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this study, despite the decreased degree of conversion observed by increasing CeO2 addition, all groups showed values around 50%, which is in accordance with commercial dental adhesives [38]. Therefore, CeO2 = 2.2 to 2.8) [30], which may have decreased the accessibility of light energy inside the polymer. The limited mobility of monomer chains by the incorporation of the opaque fillers has also been considered as a contributing factor for the decrease in the monomer's conversion [31].…”
Section: Discussionsupporting
confidence: 79%
“…The outcome observed for the degree of conversion may be attributed to the high refractive index of CeO2 (approx. ղ = 2.2 to 2.8) [30], which may have decreased the accessibility of light energy inside the polymer. The limited mobility of monomer chains by the incorporation of the opaque fillers has also been considered as a contributing factor for the decrease in the monomer's conversion [31].…”
Section: Discussionmentioning
confidence: 99%
“…But, the band gap of this oxide (3.6-3.8 eV) is higher than pure ZnO (3.37 eV). Thus, the band gap energy of Ce-ZnO film was measured greater than pure ZnO as also reported by others [34,35]. The variation of band gap energy with cerium concentration is shown in Fig.…”
Section: Optical Measurementssupporting
confidence: 82%
“…C erium dioxide (CeO 2 ) has been of great interest during the last years due to its multiple applications in several key areas of thin film technology. This material has a cubic fluorite‐type crystal structure (lattice spacing 0.5411 nm) and combines a large bandgap (<3.5 eV) with a high dielectric constant (ɛ≈26), high ionic conductivity, and high‐temperature stability 1–8 . Because of its chemical stability and close lattice parameter matching with silicon (0.35% lattice matching), CeO 2 has potential applicability in the area of optoelectronics: in silicon‐on‐insulator structures, stable capacitor devices for large‐scale integration, photoelectrodes in dye‐sensitized solar cells, and stable buffer layers between high‐temperature superconducting materials and silicon substrates 6–14 .…”
Section: Introductionmentioning
confidence: 99%